Impact of informational demand on the process of web-communities positioning - Слобода, Катерина Олегівна (Eastern-European Journal of Enterprise Technologies, 2012)
The rapid development of information technologies led to the emergence of the concept of "information society" and "information era", in which information and data play a major role. Information needs of people are growing daily. Modern society produces and uses vast amounts of information, which in turn becomes the basis for the emergence of new information requirements. As information technology allow you to search and access information extremely rapidly, using the Internet, and in particular search engines is one of the main ways to meet the information needs of people. Information search is the process of the extraction of information from information sources. Ways to find information differ significantly, depending on user needs. Search engine user behavior is the process of information retrieval. Formalizing of search behavior of users is an important task in the process of positioning of web-communities. The rapid annual growths of content that users create in the World Wide Web cause that the owners of web communities face a daunting task of positioning of these communities. The information needs of users and their desire to meet these information needs should be taken into account during the process of positioning and creation of semantic core of web-community